ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN: (STUDI KASUS ERMA LAUNDRY KELURAHAN MIMBAAN SITUBONDO) - Anas Arisandi; Agusti Agusti; Fathor Rahman (MANAJEMEN, 2025)
This study aims to analyze service quality in relation to customer satisfaction at Erma Laundry in Mimbaan Village, Situbondo. The background of this study is based on the importance of service quality in the service industry, particularly laundry services, which directly influences customer satisfaction and loyalty levels. This study uses a qualitative approach with a case study method. Data collection techniques were conducted through observation, interviews, and documentation of 19 customers and 1 business owner. The results of the study indicate that the five dimensions of service quality, namely reliability, responsiveness, assurance, empathy, and tangibles, have been consistently applied at Erma Laundry. Customers are satisfied with the fast service, clean and fragrant laundry results, friendly staff attitudes, and the cleanliness and comfort of the business premises. Although there are minor challenges during peak service periods, these do not significantly impact satisfaction. This study concludes that service quality positively influences customer satisfaction and is a key factor in building customer loyalty.